Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1159/000477846
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Cholesterol Level Relates to Working Memory, Immediate and Delayed Cued Recall in Brazilian Older Adults: The Role of Cognitive Reserve

Abstract: Aims: The present study set out to investigate the relation of the high-density lipoprotein cholesterol (HDL-C) level to cognitive performance and its interplay with key markers of cognitive reserve in a large sample of older adults. Methods: We assessed tests of working memory, immediate and delayed cued recall in 701 older adults from Amazonas, Brazil. The HDL-C level was derived from fasting blood samples. In addition, we interviewed individuals on their education, past occupation, and cognitive leisure act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
5
20
0
1
Order By: Relevance
“…Specifically, the relations of psychological stress to cognitive performance were reduced in individuals with higher education, a higher cognitive level of the first profession practiced after education, a larger number of midlife leisure activities, a larger number of significant family members, and a larger number of close friends. This is in line with studies showing that cognitive reserve and social capital may offset the detrimental influences of physiological stress on cognitive functioning in old age [2, 12, 21, 36] and extends prior evidence suggesting that the relation of psychological stress to cognitive functioning is smaller in individuals with higher scores in a late-life proxy of cognitive reserve [37], with data based on a comprehensive set of key life course markers of cognitive reserve and social capital in a large sample of older adults in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Specifically, the relations of psychological stress to cognitive performance were reduced in individuals with higher education, a higher cognitive level of the first profession practiced after education, a larger number of midlife leisure activities, a larger number of significant family members, and a larger number of close friends. This is in line with studies showing that cognitive reserve and social capital may offset the detrimental influences of physiological stress on cognitive functioning in old age [2, 12, 21, 36] and extends prior evidence suggesting that the relation of psychological stress to cognitive functioning is smaller in individuals with higher scores in a late-life proxy of cognitive reserve [37], with data based on a comprehensive set of key life course markers of cognitive reserve and social capital in a large sample of older adults in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we found that higher education, a higher cognitive level of the job, and greater engaging in leisure activities were related to better performance in the cognitive performance measures. This confirms the conceptual view that cognitive stimulation throughout the life course may contribute to cognitive reserve, thereby being related to better cognitive functioning in old age [2-17]. In line with prior evidence [20-26], we also found that having a larger number of significant family members and close friends was related to better cognitive performance, further corroborating the view that social capital is an important reserve in old age [18, 19, 45].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Dyslipidaemia also appears to cause POCD in animal studies 46. Further, dyslipidaemia is a relatively well-established risk factor for age-related cognitive impairment 7. On that basis, we had expected to find a link to POCD and can only speculate as to underlying reasons.…”
Section: Discussionmentioning
confidence: 98%